2018
DOI: 10.1002/jbt.22262
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between SALL4 stemness marker and bone morphogenetic protein signaling genes in esophageal squamous cell carcinoma

Abstract: SALL4, as a stemness marker, plays a key role in the maintenance of pluripotency and self‐renewal of cancer stem cells. To elucidate probable linkage between SALL4 stemness marker and bone morphogenetic protein (BMP) cell signaling pathway, we aimed to analyze the expression levels of the related genes in esophageal squamous cell carcinoma (ESCC) patients. Tumoral and corresponding margin normal tissues from 50 treatment‐naive ESCC patients were subjected for expression analysis using relative comparative real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Importantly, we demonstrated that the choriocarcinoma-associated transcription factor Sall4 was increased in situ in the postmolar choriocarcinoma cohort compared to that of the complete mole counterpart. This finding is in line with previous studies demonstrating that Sall4 plays a key role in tumorigenesis and tumor cell invasiveness through its correlation with TGF-β signaling genes [24,25].…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, we demonstrated that the choriocarcinoma-associated transcription factor Sall4 was increased in situ in the postmolar choriocarcinoma cohort compared to that of the complete mole counterpart. This finding is in line with previous studies demonstrating that Sall4 plays a key role in tumorigenesis and tumor cell invasiveness through its correlation with TGF-β signaling genes [24,25].…”
Section: Discussionsupporting
confidence: 93%
“…SALL4 is a novel, sensitive, and specific marker for metastatic germ cell tumors and is particularly useful for detecting metastatic yolk sac tumors 60 . Also, SALL4 plays a role in the invasiveness of ESCC by regulating BMP signaling genes 54 . In summary, these findings indicate that SALL4 is highly expressed in various types of cancer, and interference with SALL4 expression could effectively inhibit cancer metastasis.…”
Section: The Oncogenic Roles Of Sall4 In Cancermentioning
confidence: 79%
“…Moreover, SALL4 regulates the proliferation, apoptosis, cell cycle, and clonogenicity of ESCC cells 38 . For instance, SALL4 regulates bone morphogenetic protein (BMP) signaling transcription factors, as well as its target gene death‐inducer obliterator 1 ( DIDO1), to maintain the balance between tumor cell proliferation and apoptosis during ESCC tumorigenesis 54 …”
Section: The Oncogenic Roles Of Sall4 In Cancermentioning
confidence: 99%
“…Several mutation-driver genes (Mut-driver-genes) have been characterized in cancer cells so far (e.g., KRAS , BRAF , MYC , TP53 ), however vsDPGs have gained attention in the process of carcinogenesis due to their tumorigenic potential [ 145 , 146 , 147 ]. VENTX and NANOG were found highly expressed in brain (glioma/glioblastoma) [ 148 , 149 , 150 ], pancreatic [ 151 , 152 , 153 ] renal [ 154 , 155 ], esophageal [ 156 , 157 ] and testicular cancers [ 28 , 158 , 159 ]. Interestingly, VENTX and NANOG share activity in hematopoiesis by repressing the genes responsible for terminal differentiation (e.g., TAL1 , KLF1 ) [ 160 , 161 ], as well as promoting leukemia [ 161 , 162 , 163 ].…”
Section: Developmental Potential Guardians In Human Diseasesmentioning
confidence: 99%